2009
DOI: 10.1103/physrevlett.102.146103
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Coarsening of Ion Beam Ripple Patterns by Defect Annihilation

Abstract: Ripple patterns formed on Pt(111) through grazing incidence ion beam erosion coarsen rapidly. At and below 450 K coarsening of the patterns is athermal and kinetic, unrelated to diffusion and surface free energy. Similar to the situation for sand dunes, coarsening takes place through annihilation reactions of mobile defects in the pattern. The defect velocity derived on the basis of a simple model agrees quantitatively with the velocity of monatomic steps illuminated by the ion beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Figure 7(a) and Figure 10(b)). This is in contrast to other experimental systems like Pt(111) surfaces under grazing incidence sputtering where rapid coarsening proceeds due to the annihilation of defects [109]. …”
Section: Morphology Of Ion-sputtered Si Surfacesmentioning
confidence: 58%
“…Figure 7(a) and Figure 10(b)). This is in contrast to other experimental systems like Pt(111) surfaces under grazing incidence sputtering where rapid coarsening proceeds due to the annihilation of defects [109]. …”
Section: Morphology Of Ion-sputtered Si Surfacesmentioning
confidence: 58%
“…For somewhat smaller ion incidence angles, most ions are still reflected in the forward direction and result in a distinct forward sputtering of initial topographic defects, especially at the upstream side of concave surface regions (depressions). The defect size grows in the direction of ion beam, probably accompanied by a guiding of ions along the defects, similar to the formation of perpendicular mode ripples on metallic surfaces at 83 • via a network of coalesced elongated vacancy islands [66,67].…”
Section: Role Of Surface-gradient-dependent Sputtering and Reflectionmentioning
confidence: 91%
“…20 This results in step arrays parallel to the beam and subsequent formation of ripples whose separation tend to increase with irradiation duration. 21 The studies reported here on TiO 2 are the first studies of this kind on a metal oxide. Previous studies of structure formation by grazing ion beams concentrated on metal surfaces [17][18][19]21,22 and ionic crystals such as CaF 2 ͑111͒ 15, 16 and KBr͑001͒.…”
Section: Introductionmentioning
confidence: 90%
“…21 The studies reported here on TiO 2 are the first studies of this kind on a metal oxide. Previous studies of structure formation by grazing ion beams concentrated on metal surfaces [17][18][19]21,22 and ionic crystals such as CaF 2 ͑111͒ 15, 16 and KBr͑001͒. 23 While the studies on Pt͑111͒ by the Michely group are comprehensive, the main question this present study addresses is if the same processes are applicable to more complex materials such as covalent/ionic bonded oxides, i.e., materials for which single-crystal wafers have potential applications, such as thin-film substrates.…”
Section: Introductionmentioning
confidence: 90%